Filtering and acquisition of serial data frames using xilinx system generator - Adrián Gonzalo Stacul (Institute of Advanced Engineering and Science, 2020)
The main purpose of this paper is the design, development and implementation of a PCM bit-synchronizer based on a System Generator and Simulink model. The entire system will be applied to a ground station with an ad-hoc telemetric data acquisition system to be applied in UAV monitoring and sounding rockets. Based on this information, the ground station will compute the platform trajectories, velocities and attitudes.